Structural characterization and dielectric properties of bis(4-acetylanilinium) tetrachlorocadmiate, [C8H10NO]2[CdCl4]. (9th March 2015) - Jellibi, A.; Chaabane, I.; Guidara, K.
Graphical abstract: A new organic–inorganic compound, bis(4-acetylanilinium) tetrachlorocadmiate, has been synthesized and characterized by single-crystal X-ray diffraction, thermal analysis and dielectric measurements. The title compound crystallizes at room temperature in the orthorhombic system ( Cmca space group) with the following unit cell parameters: a = 19.9803(5) Å, b = 15.3829(3) Å, c = 13.8168(3) Å and Z = 8. Abstract: The new organic inorganic compound [C8 H10 NO]2 CdCl4 crystallizes at room temperature in the orthorhombic system ( CmCa space group) with the following unit cell parameters: a = 19.9803(5) Å, b = 15.3829(3) Å, c = 13.8168(3) Å and Z = 8. The atomic arrangement can be described as an alternation of organic/inorganic layers along the a direction. The organic layer is built up by one type of [C8 H10 NO] + cation and the inorganic layer is built up by isolated and distorted tetrahedral CdCl4 2− anions. The TGA–DTA curves revealed two endothermic peaks. The first peak may be due to a phase transition, while the second peak corresponds to the decomposition point. Additionally analysis of the dielectric constants ε ′ and ε ″ versus temperature at several frequencies shows a relaxation process which could be due to disorder in the lattice.